A Permanent-Magnet Eddy-Current Loss Analytical Model for Axial Flux Permanent-Magnet Electric Machine Accounting for Stator Saturation - Hao Liu; Jin Tian; Guofeng He; Xiaopeng Li (Energies)
This paper introduces a hybrid analytical model (HAM) for the evaluation of permanent-magnet (PM) eddy-current loss in dual-stator single-rotor axial flux permanent-magnet machine (AFPMM), accounting for stator saturation. The proposed model integrates the magnetic equivalent circuit (MEC) with an analytical model based on scalar magnetic potential, enabling simultaneous consideration of different rotor positions and stator slotting effects. The three-dimensional finite element method (3D-FEM) validates the no-load and armature reaction magnetic field calculated by HAM, as well as the PM eddy-current loss under both no-load and load conditions. Compared to 3D-FEM, the proposed model reduces the calculation time by more than 98% with an error of no more than 18%, demonstrating a significant advantage in terms of computational time. Based on the proposed model, the effects of air-gap length and slot opening width on PM eddy-current loss are analyzed; the results indicate that reducing the slot opening width can effectively mitigate PM eddy-current loss for AFPMM.